Analysis of the Structural Organisation of the Large Raptor Community in Remdovsky Reserve - Vasiliy G. Pchelintsev; Vladimir V. Ivanovsky (Пернатые хищники и их охрана)
Questions regarding the abundance of raptor nesting population and the objectivity of the applied censusing methods have constantly caused and still cause active discussions in the scientific literature (Ivanovsky, Bashkirov, 2002, etc.). This is especially relevant during the creation of protected areas, where, undoubtedly, the size of nesting territories of “umbrella” species – large birds of prey – should be taken into account at the start. In addition to the theoretical component, this question has practical implications.